Southern comfort : a new take on the recipes we grew up with - Vines-Rushing, Allison (Ten Speed Press, 2012)
"The much-anticipated debut cookbook from two of the most admired and innovative young chefs in the South, with 100 recipes featuring their refined, classically-inspired takes on the traditional Southern food they grew up with"--